Butterflies in trouble: The effectiveness of Natura 2000 network in preventing habitat loss and population declines of endangered species in urban area. (February 2022) - Kajzer-Bonk, Joanna; Nowicki, Piotr
Highlights: Valuable habitats in urban areas are under anthropogenic pressure. Across the 20 years of study the number of habitat patches decreased twofold. Status of protected species does not guarantee proper protection. Establishment of Natura 2000 sites ensures stability of populations of focal species. Existing populations of protected species decline outside Natura 2000 sites. Abstract: Habitat deterioration and biodiversity decline is progressing worldwide. However, these effects may be somewhat mitigated in urban areas, which are strongly exposed to anthropogenic pressure. The protected sites may here impede habitat loss and serve as effective tool of biodiversity conservation. The aim of this study was to test if location (inside/outside Natura 2000 sites) and size of habitat fragments affect the habitat loss and population trends in metapopulations of three Phengaris butterflies exposed to urbanization pressure. Across 20 years of study the number of habitat patches decreased by half, mainly outside N2000 sites. Total area of available habitat decreased by 13% for P. teleius and P. nausithous butterflies, and by 21% for P. alcon . Negative population trends were observed for all three species at small and medium-size habitat patches located outside N2000 sites as well as at small patches inside N2000 sites. The existing populations appear to be vulnerable outside N2000 sites. Our findings indicate that N2000 sites fulfill their protective function in halting population loss of species of high conservation interest and effective protection of intact habitats may support urban biodiversity. Nevertheless, there is an urgent need to expand the existing protected areas in order to save remnant local populations from their imminent extinctions in near future, as the species legal protection is not effective beyond N2000 sites. As meadow habitats serve a whole range of ecosystem services, their remnants deserve to be effectively protected in urbanized areas.